2013
DOI: 10.1111/ene.12185
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of the movement disorder in methcathinone abusers: clinical,MRIand manganesemia changes, and neuropathology

Abstract: No improvement in this Mn-induced movement disorder occurs after cessation of methcathinone abuse despite improvement of Mn blood levels and/or MRI abnormalities. Ultrastructural abnormalities in a former user confirm structural damage to white matter is associated with the disorder. Methcathinone/Mn toxicity is an important, disabling and permanent medical sequel of intravenous drug abuse in the former Soviet Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Their average blood manganese levels were markedly lower and their MRI changes were less frequent and intense than those of active users. After a median period of 32.5 months, the prospective follow-up published in this issue confirms these findings [1], implying that permanent neuronal damage remained, despite resorption of manganese from the basal ganglia. This notion is enriched by the neuropathology examination of the globus pallidus biopsy from a former user, which confirmed structural damage with decompacted myelin sheaths and frequent abnormalities of mitochondria within the axons.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Their average blood manganese levels were markedly lower and their MRI changes were less frequent and intense than those of active users. After a median period of 32.5 months, the prospective follow-up published in this issue confirms these findings [1], implying that permanent neuronal damage remained, despite resorption of manganese from the basal ganglia. This notion is enriched by the neuropathology examination of the globus pallidus biopsy from a former user, which confirmed structural damage with decompacted myelin sheaths and frequent abnormalities of mitochondria within the axons.…”
supporting
confidence: 69%
“…In keeping with the follow‐up study by Stepens et al . , in another recent issue of the European Journal of Neurology , Sikk et al . .…”
mentioning
confidence: 96%
“…Intravenous injections of such methcathinone preparations expose users to a high manganese load because the resultant methcathinone is not purified [75]. Although studies of methcathinone abusers have described movement disorders similar to Parkinson’s disease attributed to the manganese toxicity, the syndrome lacks typical features of this condition such as resting tremor and gait initiation failure [75]. The accumulation of manganese can lead to the development of encephalopathy and might trigger secondary pathogenic mechanisms, such as mitochondrial dysfunction and oxidative stress [76].…”
Section: Biochemical Mechanisms: Oxidative Stress and Cytotoxicitymentioning
confidence: 99%
“…Abuse of a 'homemade' version of the psychostimulant drug methcathinone (Mcat) causes a persistent and disabling extrapyramidal syndrome (Sikk et al 2011(Sikk et al , 2013Stepens et al 2014). This shares some common features with Parkinson's disease, but has distinct symptoms including early falls, dystonia, severe dysarthria, and a poor response to l-DOPA treatment (Sikk et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This produces a solution containing high levels of both Mcat and manganese (Mn) which is then injected intravenously on multiple occasions each day (Sikk et al 2007). The neurological syndrome that appears in man is accompanied by Mn deposition in the basal ganglia and altered basal ganglia function as assessed by abnormal fluorodeoxyglucose (FDG) uptake (Sikk et al 2013;Stepens et al 2014) and decreased striatal D2 receptor binding density (Kessler et al 2003) shown by MRI and PET investigations.…”
Section: Introductionmentioning
confidence: 99%